'Drawing up a balance sheet': accounting for history in Australia. Issue 1 (2nd January 2016) - Dorman, Stefanie
Abstract : This essay undertakes a historiographical analysis of Australia's 'History Wars'. It relates these polemical debates over the politics of Australian history to concurrent disputes amongst historians concerning the motives behind Britain's settlement of the Australian mainland. In debating whether settlement was prompted by Britain's proliferating convict population or by a desire for imperial expansion, historians on both ends of the political spectrum rely on a model of historical accountability which is itself the product of innovations in economic thought made during the British Enlightenment. Without sufficient acknowledgement of or attention to the epistemological context of Australia's 'founding moment', Australian historical discourse is reproduced via conceptual models which mask its derivation from the very 'history' in question.